Law Enforcement in Dealing with the Lack of Ethics of Social Media Users by the Directorate of Cyber Crime (Dittipidsiber) Bareskrim Polri - Sitepu, Dedek Ervina; Nita, Surya; Handayani, Riska Sri (Faculty of Law, Universitas Pekalongan, 2024)
This research aims to analyze the law enforcement mechanisms carried out by the Directorate of Cyber Crime (Dittipidsiber) of the Indonesian National Police's Criminal Investigation Department (Bareskrim Polri) in facing the lack of ethics among social media users that potentially lead to cybercrimes. With a focus on handling cybercrime cases on social media, this research reveals and analyzes the steps taken by Dittipidsiber in responding to ethical violations in cyberspace. The research methodology employed is qualitative with a case study approach. Data was collected through document studies, interviews, and observations to gain a comprehensive understanding of the law enforcement processes undertaken by Dittipidsiber. Data analysis was conducted by interpreting information obtained from these sources to construct a comprehensive understanding of the research subject. The conclusions of this research indicate that Dittipidsiber Bareskrim Polri has implemented a series of repressive and preventive efforts to address cybercrimes. These efforts include law enforcement, investigation, prosecution, infrastructure improvement, education and training, socialization and education, sanctions enforcement, as well as international cooperation. Additionally, the mechanisms for handling cybercrime cases involve both criminal and non-criminal legal policies, digital forensic analysis, and service optimization to prevent criminal activities, based on the Electronic Information and Transactions Law (UU ITE). Education and socialization to the public also play a crucial role in preventing cybercrimes.